Low-deformation high-performance ceramic chopper dry pressing powder formula and preparation method thereof
By optimizing the formula and preparation process of ceramic splitter dry pressing powder, using raw materials such as α-Al2O3 and additives such as nano SiO2, the problems of high deformation and insufficient mechanical properties of traditional ceramic splitter dry pressing powder during sintering are solved, and the problem of high deformation and insufficient mechanical properties of traditional ceramic splitter dry pressing powder during sintering is achieved. It has low deformation, low shrinkage, high strength and high toughness, and is suitable for semiconductor packaging fields.
Patent Information
- Application Number
- CN202411152871.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the sintering process, traditional ceramic splitting knife dry pressing powder has high deformation, uneven grain growth, grain boundary defects and poor fluidity and pressing performance, which affects the dimensional accuracy, shape stability and mechanical properties of the material.
The formula of raw materials such as α-Al2O3, nano SiO2, MgO, Y2O3, ZrO2, Cr2O3, PVA and PEG was prepared by ball milling, spray drying, granulation, dry screening, dry press forming and sintering. The ceramic splitter is dry-pressed with powder, optimized sintering process to reduce deformation and shrinkage and improve mechanical properties.
It significantly reduces the sintering deformation and shrinkage rate, improves the mechanical properties and dimensional accuracy of the material, and provides a ceramic splitter dry pressing powder with better performance and higher stability, suitable for semiconductor packaging fields.
Smart Images

Figure BDA0005004109990000091 
Figure BDA0005004109990000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and in particular relates to a low-deformation high-performance ceramic splitter dry-pressed powder formula and a preparation method thereof. Background Art
[0002] Ceramic splitter dry pressed powder is a powder raw material used to make ceramic splitters, which play a vital role in the field of semiconductor packaging. It is mainly used as a bonding tool to perform gold wire bonding between chips and lead frames. This process realizes the metallurgical bonding between the gold wire and the pad, thereby ensuring the electrical connection between the chip and the lead frame. This bonding method is efficient, reliable and adaptable, and is an indispensable part of the semiconductor packaging process.
[0003] There are several shortcomings in the preparation process of traditional ceramic splitter dry-pressed powder: 1) High sintering temperature: Traditional formulas often require high sintering temperatures to ensure sufficient densification, which may cause large deformation of the material during the sintering process, affecting the dimensional accuracy and shape stability of the product. High-temperature sintering may also cause the accumulation of internal stress in the material, further exacerbating the deformation problem. 2) Uneven grain growth: The lack of effective grain growth inhibitors may lead to abnormal grain growth during the sintering process, which will reduce the overall strength and toughness of the material. 3) Grain boundary defects: The lack of appropriate additives to stabilize the grain boundaries may cause grain boundary sliding or other defects, affecting the mechanical properties of the material. 4) Poor fluidity and pressing performance: Using only polyvinyl alcohol (PVA) as an organic additive is not enough to provide the best powder fluidity and pressing performance, which in turn affects the density and performance of the final product. For this reason, a low-deformation, high-performance ceramic splitter dry-pressed powder formula and its preparation method are proposed. Summary of the invention
[0004] The object of the present invention is to provide a low-deformation, high-performance ceramic splitter dry-pressed powder formula and a preparation method thereof, aiming to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A low-deformation high-performance ceramic splitting tool dry-pressed powder formula comprises the following raw materials in weight percentage: 92.5% of α-Al2O3, 3% of nano-SiO2, 0.6% of MgO, 0.4% of Y2O3, 1% of ZrO2, 0.2% of Cr2O3, 0.8% of PVA, 0.5% of PEG and 1% of water.
[0007] A method for preparing the low-deformation high-performance ceramic splitter dry-pressed powder according to the above-mentioned method comprises the following steps:
[0008] Step 1, ball milling mixing;
[0009] Step 2, spray drying;
[0010] Step 3, preparation of organic additives;
[0011] Step 4, granulation;
[0012] Step 5, drying and screening;
[0013] Step 6: dry pressing;
[0014] Step 7: sintering;
[0015] Step 8, post-processing;
[0016] Step 9, performance test: Test according to ASTM standards, including density test, bending strength test, fracture toughness test and hardness test.
[0017] Furthermore, the specific steps of step 1 are as follows:
[0018] a. Weigh the raw materials according to the formula and add them into a 5L zirconia ball mill;
[0019] b. Add anhydrous ethanol at a solid-liquid ratio of 1:1.5;
[0020] c. Add zirconia balls according to the ball-to-material ratio of 3:1;
[0021] d. Seal the ball mill, install the ball mill on the planetary ball mill, and start ball milling at a speed of 300 rpm;
[0022] e. During the ball milling process, change the rotation direction every 2 hours;
[0023] f. Stop ball milling after 24 hours and let it stand for 2 hours.
[0024] Furthermore, the specific steps of step 2 are as follows:
[0025] a. Filter the ball-milled slurry through a 200-mesh sieve;
[0026] b. Adjust the parameters of the centrifugal spray dryer to the set values, including atomization pressure: 0.2MPa, inlet temperature: 180℃, outlet temperature: 90-95℃, centrifugal disc speed: 12000rpm;
[0027] c. Start feeding and control the feeding rate to 50ml / min;
[0028] d. Collect the dried powder and control the moisture content of the powder to <0.5%.
[0029] Furthermore, the specific steps of step 3 are as follows:
[0030] a. Heat deionized water to 80°C;
[0031] b. Slowly add PVA, stir to dissolve, and maintain the temperature for 1h;
[0032] c. Cool down to 60°C, add PEG, and continue stirring for 30 minutes;
[0033] d. Cool naturally to room temperature to obtain a 5 wt% organic additive solution.
[0034] Furthermore, the specific steps of step 4 are as follows:
[0035] a. Mix the spray-dried powder with the organic additive solution in a weight ratio of 95:5;
[0036] b. Stir evenly and let stand for 2 hours to allow the powder to fully absorb the organic additives;
[0037] c. Add the mixed powder into the hopper of the extrusion granulator;
[0038] d. Start the granulator and control the extrusion pressure to 5MPa;
[0039] e. Adjust the granulation disk speed to 50rpm and start granulation;
[0040] f. Collect the granulated particles and control the particle size within the range of 100-200 μm.
[0041] Furthermore, the specific steps of step 5 are as follows:
[0042] a. Spread the granulated particles evenly on the drying plate with a thickness not exceeding 1 cm;
[0043] b. Preheat the hot air circulation oven to 60°C, place the drying tray with the granules in the preheated oven, and dry for 12 hours;
[0044] c. Take out the dried particles and cool them to room temperature;
[0045] d. The vibrating screening machine uses an 80-mesh screen for screening, and the vibration time is 15 minutes;
[0046] e. Collect the material under the sieve, which is the final dry pressed powder.
[0047] Furthermore, the specific steps of step 6 are as follows:
[0048] a. Load the dry pressed powder into the mold and vibrate gently to evenly distribute the powder;
[0049] b. Place the mold into the hydraulic press and slowly pressurize it to 200MPa;
[0050] c. After maintaining the pressure for 30 seconds, slowly release the pressure at a rate of 0.5MPa / s;
[0051] d. Take out the green billet.
[0052] Furthermore, the specific steps of step 7 are as follows:
[0053] a. Place the dry pressed green body into an alumina crucible;
[0054] b. Place the alumina crucible in the center of the high temperature box furnace;
[0055] c. Sintering is performed according to the set sintering curve; the sintering temperature curve is: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping warm for 2h, then continuing to heat to 1200°C at a heating rate of 5°C / min. When the furnace temperature reaches 1200°C, continue to heat to 1600°C at a heating rate of 3°C / min, keeping warm for 4h.
[0056] d. After sintering is completed, start cooling at a cooling rate of 2°C / min. When the furnace temperature drops below 200°C, open the furnace and take out the sample.
[0057] Furthermore, the specific steps of step 8 are as follows:
[0058] a. Fix the sintered sample on the grinder workbench;
[0059] b. Perform surface fine grinding to remove the surface sintering layer, the grinding speed is 30m / s, and the feed rate is 0.01mm / time;
[0060] c. Clean the sample with an ultrasonic cleaner for 15 minutes to remove grinding residues;
[0061] d. Dry at 60℃ for 2h.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The present invention has successfully developed a low-deformation, low-shrinkage, high-performance ceramic splitter dry-pressed powder through innovative formula design and optimized preparation process. While maintaining the advantages of traditional high-purity alumina, this material significantly improves sintering deformation, shrinkage and mechanical properties, providing a key material with better performance and higher stability for the semiconductor packaging field, with important practical value and broad application prospects. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0065] One embodiment of the present invention provides a method for preparing a low-deformation high-performance ceramic splitter dry-pressed powder formula, comprising the following steps:
[0066] 1. Raw material preparation;
[0067] Accurately weigh the following ingredients:
[0068] High-purity α-Al2O3 (purity ≥ 99.99%, D50 = 0.5 μm): 925 g;
[0069] Nano-SiO2 (purity ≥ 99.5%, particle size 20-30nm): 30g;
[0070] MgO (purity ≥ 99.9%, D50 = 0.8 μm): 6 g;
[0071] Y2O3 (purity ≥ 99.99%, D50 = 1.0 μm): 4 g;
[0072] ZrO2 (purity ≥ 99.9%, D50 = 0.3 μm): 10 g;
[0073] Cr2O3 (purity ≥ 99.9%, D50 = 0.5 μm): 2 g.
[0074] 2. Ball milling and mixing. The operation steps are as follows:
[0075] a. Weigh the raw materials according to the formula and add them into a 5L zirconia ball mill;
[0076] b. Add anhydrous ethanol at a solid-liquid ratio of 1:1.5;
[0077] c. Add zirconia balls with a diameter of 5 mm according to the ball-to-material ratio of 3:1;
[0078] d. Seal the ball mill, install the ball mill on the planetary ball mill, and start ball milling at a speed of 300 rpm;
[0079] e. During the ball milling process, change the rotation direction every 2 hours;
[0080] f. Stop ball milling after 24 hours and let it stand for 2 hours.
[0081] 3. Spray drying, the operation steps are as follows:
[0082] a. Filter the ball-milled slurry through a 200-mesh sieve;
[0083] b. Adjust the parameters of the centrifugal spray dryer to the set values, including atomization pressure: 0.2MPa, inlet temperature: 180℃, outlet temperature: 90-95℃, centrifugal disc speed: 12000rpm;
[0084] c. Start feeding and control the feeding rate to 50ml / min;
[0085] d. Collect the dried powder and control the moisture content of the powder to <0.5%.
[0086] 4. Preparation of organic additives;
[0087] raw material:
[0088] Polyvinyl alcohol (PVA, molecular weight 72000): 40 g;
[0089] Polyethylene glycol (PEG, molecular weight 4000): 25 g;
[0090] Deionized water: 1335 g.
[0091] The steps are as follows:
[0092] a. Heat deionized water to 80°C;
[0093] b. Slowly add PVA, stir to dissolve, and maintain the temperature for 1h;
[0094] c. Cool down to 60°C, add PEG, and continue stirring for 30 minutes;
[0095] d. Cool naturally to room temperature to obtain a 5 wt% organic additive solution.
[0096] 5. Granulation, the operation steps are as follows:
[0097] a. Mix the spray-dried powder with the organic additive solution in a weight ratio of 95:5;
[0098] b. Stir evenly and let stand for 2 hours to allow the powder to fully absorb the organic additives;
[0099] c. Add the mixed powder into the hopper of the extrusion granulator;
[0100] d. Start the granulator and control the extrusion pressure to 5MPa;
[0101] e. Adjust the granulation disk speed to 50rpm and start granulation;
[0102] f. Collect the granulated particles and control the particle size within the range of 100-200 μm.
[0103] 6. Drying and screening. The operation steps are as follows:
[0104] a. Spread the granulated particles evenly on the drying plate with a thickness not exceeding 1 cm;
[0105] b. Preheat the hot air circulation oven to 60°C, place the drying tray with the granules in the preheated oven, and dry for 12 hours;
[0106] c. Take out the dried particles and cool them to room temperature;
[0107] d. The vibrating sieving machine uses an 80-mesh (177 μm) sieve for sieving, and the vibration time is 15 min;
[0108] e. Collect the material under the sieve, which is the final dry pressed powder.
[0109] 7. Dry pressing molding, the operation steps are as follows:
[0110] a. Load the dry pressed powder into the mold and vibrate gently to evenly distribute the powder;
[0111] b. Place the mold into the hydraulic press and slowly pressurize it to 200MPa;
[0112] c. After maintaining the pressure for 30 seconds, slowly release the pressure at a rate of 0.5MPa / s;
[0113] d. Take out the green billet.
[0114] 8. Sintering, the operation steps are as follows:
[0115] a. Place the dry pressed green body into an alumina crucible;
[0116] b. Place the alumina crucible in the center of the high temperature box furnace;
[0117] c. Sintering is performed according to the set sintering curve: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then continuing to heat to 1200°C at a heating rate of 5°C / min. When the furnace temperature reaches 1200°C, continue to heat to 1600°C at a heating rate of 3°C / min, and keep the temperature for 4 hours;
[0118] d. After sintering is completed, start cooling at a cooling rate of 2°C / min. When the furnace temperature drops below 200°C, open the furnace and take out the sample.
[0119] 9. Post-processing, the operation steps are as follows:
[0120] a. Fix the sintered sample on the grinder workbench;
[0121] b. Perform surface fine grinding to remove the surface sintering layer, the grinding speed is 30m / s, and the feed rate is 0.01mm / time;
[0122] c. Clean the sample with an ultrasonic cleaner for 15 minutes to remove grinding residues;
[0123] d. Dry at 60℃ for 2h.
[0124] 10. Performance test: Tests are conducted in accordance with ASTM standards, including density test (ASTM C373), flexural strength test (ASTM C1161), fracture toughness test (ASTM C1421) and hardness test (ASTM C1327).
[0125] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0126] Example 1, comparison of sintering deformation rate;
[0127] Sample preparation: 10 samples with a size of 100 mm×10 mm×10 mm were prepared using the formula of the present invention and the traditional formula respectively.
[0128] Condition settings: dry pressing pressure: 200MPa; sintering temperature: 1600℃; holding time: 4h.
[0129] 2) Measurement method: Use a precision micrometer to measure the length, width and thickness of the sample before and after sintering, and calculate the deformation rate.
[0130] 3) Results:
[0131] Formula of the present invention: average deformation rate 0.21±0.03%;
[0132] Traditional formula: average deformation rate 1.48±0.12%.
[0133] The results show that the sintering deformation rate of the present invention's formula (0.21%) is significantly lower than that of the traditional formula (1.48%), which is reduced by about 86%. This is mainly due to the addition of nano-SiO2 and the synergistic effect of Y2O3 and ZrO2, which effectively inhibits deformation at high temperatures.
[0134] Example 2, sintering shrinkage comparison;
[0135] 1) Sample preparation: Ten disc samples with a diameter of 50 mm and a thickness of 5 mm were prepared using the formula of the present invention and the traditional formula respectively.
[0136] Condition settings: dry pressing pressure: 200MPa; sintering temperature: 1600℃; holding time: 4h.
[0137] 2) Measurement method: Use a precision caliper to measure the diameter and thickness of the sample before and after sintering, and calculate the linear shrinkage.
[0138] 3) Results:
[0139] The formula of the present invention has an average linear shrinkage of 14.6±0.2%.
[0140] Traditional formula: average linear shrinkage 17.7±0.4%.
[0141] The results show that the linear shrinkage of the formula of the present invention (14.6%) is about 17.5% lower than that of the traditional formula (17.7%). This is due to the precise addition of Cr2O3, which forms a pinning effect at the grain boundary, regulates the sintering dynamics, and achieves a more uniform shrinkage. The low shrinkage helps to improve dimensional accuracy and reduce subsequent processing steps.
[0142] Example 3, mechanical properties comparison;
[0143] 1) Sample preparation: Prepare test bars of 3 mm × 4 mm × 45 mm according to ASTM C1161 standard, 20 pieces per group.
[0144] 2) Test items and methods:
[0145] a. Bending strength: three-point bending method, span 40mm, loading rate 0.5mm / min;
[0146] b. Fracture toughness: SENB method (single-edge notched beam method), notch depth 2 mm;
[0147] c. Vickers hardness: load 9.8N, holding time 15s.
[0148] 3) The results are shown in Table 1:
[0149] Table 1 Comparison of mechanical properties between the formula of the present invention and the traditional formula
[0150]
[0151]
[0152] From the results in Table 1, it can be seen that the formula of the present invention is superior to the traditional formula in various mechanical properties:
[0153] Flexural strength increased by 15.6% (520MPa vs 450MPa);
[0154] Fracture toughness increased by 23.1% (4.8MPa·m^0.5 vs 3.9MPa·m^0.5);
[0155] Vickers hardness increased by 7.1% (19.5GPa vs 18.2GPa);
[0156] These improvements are mainly attributed to the fine grain strengthening and phase transformation toughening of ZrO2, which give the material better mechanical properties and service life.
[0157] Example 4, microstructure analysis;
[0158] 1) Sample preparation: The sintered samples were cut, ground, polished, and thermally etched (1550°C, 30 min).
[0159] 2) Analysis method: The grain size and distribution were observed using a scanning electron microscope (SEM).
[0160] 3) Results:
[0161] The formula of the present invention has an average grain size of 2.5±0.3 μm and is evenly distributed.
[0162] Traditional formula: average grain size 5.8±0.7μm, with abnormally grown grains.
[0163] The results show that the average grain size (2.5 μm) of the invention is significantly smaller than that of the conventional formula (5.8 μm), and the distribution is more uniform, without abnormally grown grains. This fine-grained and uniform microstructure is a key factor in low deformation and high strength.
[0164] It can be seen from the above embodiments that the advantages of the present invention are as follows:
[0165] Process controllability: By precisely controlling the addition ratio of each component and optimizing the preparation process, the formula of the present invention exhibits good repeatability and stability. The performance fluctuation between batches is significantly smaller than that of traditional formulas, which is conducive to large-scale production and quality control.
[0166] Improved comprehensive performance: The formula of the present invention maintains the characteristics of the high-purity alumina matrix, and through the synergistic effect of multiple additives, achieves the comprehensive performance improvement of low deformation, low shrinkage, high strength and high toughness. This makes the material very suitable for making ceramic splitters for semiconductor packaging with strict requirements.
[0167] Economic benefits: Although the formula of the present invention adds some additives and slightly increases the cost of raw materials, it significantly reduces the sintering deformation rate and shrinkage rate, greatly improves the yield rate (estimated to be increased by more than 20%), thereby reducing the overall production cost. At the same time, the excellent mechanical properties also extend the service life of the product and improve customer satisfaction.
[0168] Application prospects: The low-deformation, high-performance ceramic splitter dry-pressed powder prepared by the present invention is not only suitable for the field of semiconductor packaging, but can also be extended to other fields that require high-precision, high-performance ceramic components, such as precision optical devices, high-temperature structural parts, etc.
[0169] In summary, the present invention has successfully developed a low-deformation, low-shrinkage, high-performance ceramic splitter dry-pressed powder through innovative formula design and optimized preparation process. While maintaining the advantages of traditional high-purity alumina, this material significantly improves sintering deformation, shrinkage and mechanical properties, providing a key material with better performance and higher stability for the semiconductor packaging field, with important practical value and broad application prospects.
[0170] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A low-deformation high-performance ceramic splitter dry pressed powder, characterized in that: The invention comprises the following raw materials in weight percentage: 92.5% of α-Al2O3, 3% of nano-SiO2, 0.6% of MgO, 0.4% of Y2O3, 1% of ZrO2, 0.2% of Cr2O3, 0.8% of PVA, 0.5% of PEG and 1% of water.
2. A method for preparing low-deformation high-performance ceramic splitter dry pressed powder according to claim 1, characterized in that: The following steps are involved: Step 1, ball milling mixing; Step 2, spray drying; Step 3, preparation of organic additives; Step 4, granulation; Step 5, drying and screening; Step 6: dry pressing; Step 7: sintering; Step 8, post-processing; Step 9, performance test: Test according to ASTM standards, including density test, bending strength test, fracture toughness test and hardness test.
3. The preparation method according to claim 2, characterized in that: The specific steps of step 1 are as follows: a. Weigh the raw materials according to the formula and add them into a 5L zirconia ball mill; b. Add anhydrous ethanol at a solid-liquid ratio of 1:1.5; c. Add zirconia balls according to the ball-to-material ratio of 3:1; d. Seal the ball mill, install the ball mill on the planetary ball mill, and start ball milling at a speed of 300 rpm; e. During the ball milling process, change the rotation direction every 2 hours; f. Stop ball milling after 24 hours and let it stand for 2 hours.
4. The preparation method according to claim 3, characterized in that: The specific steps of step 2 are as follows: a. Filter the ball-milled slurry through a 200-mesh sieve; b. Adjust the parameters of the centrifugal spray dryer to the set values, including atomization pressure: 0.2MPa, inlet temperature: 180℃, outlet temperature: 90-95℃, centrifugal disc speed: 12000rpm; c. Start feeding and control the feeding rate to 50ml / min; d. Collect the dried powder and control the moisture content of the powder to <0.5%.
5. The preparation method according to claim 4, characterized in that: The specific steps of step 3 are as follows: a. Heat deionized water to 80°C; b. Slowly add PVA, stir to dissolve, and maintain the temperature for 1h; c. Cool down to 60°C, add PEG, and continue stirring for 30 minutes; d. Cool naturally to room temperature to obtain a 5 wt% organic additive solution.
6. The preparation method according to claim 5, characterized in that: The specific steps of step 4 are as follows: a. Mix the spray-dried powder with the organic additive solution in a weight ratio of 95:5; b. Stir evenly and let stand for 2 hours to allow the powder to fully absorb the organic additives; c. Add the mixed powder into the hopper of the extrusion granulator; d. Start the granulator and control the extrusion pressure to 5MPa; e. Adjust the granulation disk speed to 50rpm and start granulation; f. Collect the granulated particles and control the particle size within the range of 100-200 μm.
7. The preparation method according to claim 6, characterized in that: The specific steps of step 5 are as follows: a. Spread the granulated particles evenly on the drying plate with a thickness not exceeding 1 cm; b. Preheat the hot air circulation oven to 60°C, place the drying tray with the granules in the preheated oven, and dry for 12 hours; c. Take out the dried particles and cool them to room temperature; d. The vibrating screening machine uses an 80-mesh screen for screening, and the vibration time is 15 minutes; e. Collect the material under the sieve, which is the final dry pressed powder.
8. The preparation method according to claim 7, characterized in that: The specific steps of step 6 are as follows: a. Load the dry pressed powder into the mold and vibrate gently to evenly distribute the powder; b. Place the mold into the hydraulic press and slowly pressurize it to 200MPa; c. After maintaining the pressure for 30 seconds, slowly release the pressure at a rate of 0.5MPa / s; d. Take out the green billet.
9. The preparation method according to claim 8, characterized in that: The specific steps of step 7 are as follows: a. Place the dry pressed green body into an alumina crucible; b. Place the alumina crucible in the center of the high temperature box furnace; c. Sintering is performed according to the set sintering curve; the sintering temperature curve is: heating from room temperature to 500°C at a heating rate of 2°C / min, keeping warm for 2h, then continuing to heat to 1200°C at a heating rate of 5°C / min. When the furnace temperature reaches 1200°C, continue to heat to 1600°C at a heating rate of 3°C / min, keeping warm for 4h. d. After sintering is completed, start cooling at a cooling rate of 2°C / min. When the furnace temperature drops below 200°C, open the furnace and take out the sample.
10. The preparation method according to claim 9, characterized in that: The specific steps of step 8 are as follows: a. Fix the sintered sample on the grinder workbench; b. Perform surface fine grinding to remove the surface sintering layer, the grinding speed is 30m / s, and the feed rate is 0.01mm / time; c. Clean the sample with an ultrasonic cleaner for 15 minutes to remove grinding residues; d. Dry at 60℃ for 2h.
Citation Information
Patent Citations
Ceramic body as well as preparation method and application thereof
CN107382289A
Aluminum oxide ceramic skeleton for transformer and preparation method thereof
CN112094108A
High-temperature creep-resistant ceramic material and preparation method thereof
CN113880563A
Preparation method of high-hardness fine-grain ZTA system multiphase ceramic material
CN114031376A
High-performance aluminum oxide ceramic chopper and preparation method thereof
CN116003109A
